TELEWORKING: A FLEXIBILITY OF THE CONCEPT OF SUBORDINATION IN THE LABOR REFORM (Reflection and Critique Law Magazine, 2020)
When we speak of a labor activity by itself, it already has social relevance, since decent work is the right of the individual, established and guaranteed by the International Labor Organization (ILO) in the year 1990. Decent work is qualified by the employment, rights, protection and dialogue between employer and employee. By purpose, all these requirements must be present in Telework, since despite not assuming a common form, it is still a work activity. The work does not run in its entirety within a company, but instead, here, work on its large margin runs out of the conventional environment.     In any case, it is important to approach the theme from a current point of view and to be in agreement with the new changes, always analyzing the positive norm, the decisions of jurisprudence and the contracts in their individualities, since we are part of a society ruled in the transformation and change of relationships.